1967
DOI: 10.1037/h0024354
|View full text |Cite
|
Sign up to set email alerts
|

Duration of chronic electroshock treatment in relation to brain weight, brain chemistry, and behavior.

Abstract: Minimal, maximal, or sham seizures were chronically administered to 168 male Wistar rats 3 or 5 times per week for 4,8,12, or 16 wk. Regional analysis of the brains revealed that increase in weight of the whole brain of electroshocked Ss reported previously was confined to the cortex-especially ventral cortex, including hippocampus and amygdala. Total protein and total AChE actively increased throughout most of the brain in proportion to increase in weight. Specific ChE activity decreased in the cortex of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1969
1969
1981
1981

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In part this reflects hepatic enzyme induction and hence increased detoxification, but a further component is " centrally mediated (Baumel, De Feo, & Lai, 1969). Similarly, electroconvulsive shock threshold rises with repetition (Pryor, Otis, Scott, & Colwell, 1967) and even the isolated cerebral cortex exhibits this type of neurostasis (Grafstein & Sastry, 1957;Sharpless & Halpern, 1962).…”
Section: Evidence For An Arousal Theorymentioning
confidence: 99%
“…In part this reflects hepatic enzyme induction and hence increased detoxification, but a further component is " centrally mediated (Baumel, De Feo, & Lai, 1969). Similarly, electroconvulsive shock threshold rises with repetition (Pryor, Otis, Scott, & Colwell, 1967) and even the isolated cerebral cortex exhibits this type of neurostasis (Grafstein & Sastry, 1957;Sharpless & Halpern, 1962).…”
Section: Evidence For An Arousal Theorymentioning
confidence: 99%
“…Additional environmental stimulation (and presumably learning) produced a decrease and increase in AChE and In connection with the first question it should be noted that the pattern of biochemical changes observed differs from that obtained following electroshock treatment during development. Pryor et al (1966) and Pryor et al (1967) observed an increase in AChE activity per unit of weight of tissue, and a decrease in ChE activity. Brain weight following both types of treatment shows a general increase.…”
Section: Discussionmentioning
confidence: 93%
“…It has been hypothesized that these biochemical changes due to developmental treatment, possibly constituting a storage system for such early learning, mediate the behavioral effects observed in the adult. Electroshock treatment during development similarly produces changes in brain weights, but leads to impaired learning and a different pattern of effects on ChE and AChE activities (Pryor, Otis, Scott, & Colwell, 1967;Pryor, Otis, & Uyeno, 1966).…”
mentioning
confidence: 99%
“…The latter has been examined in connection with its hypothesised role in memory or experiential coding (Deutsch, 1966(Deutsch, , 1969Deutsch & Leibowitz, 1966;Rosenzweig, 1966;Wiener & Deutsch, 1968) and in control of responding generally (Glow, Richardson, & Rose, 1967;Carlton, 1968Carlton, , 1969Russell, 1969). Enrichment and restriction of environmental stimulation, and probably therefore of learning (Altman & Das, 1964;Bennett, Diamond, Krech, & Rosenzweig, 1964;, 1963: Rosenzweig, Krech, Bennett, & Diamond, 1962, and electroshock treatment during development Pryor, Otis, Scott, & Colwell, 1967;Pryor, Otis, & Lyeno, 1966) have been used as experimental conditions. These results have been discussed fully by Brown (in press).…”
Section: Brown and Kingmentioning
confidence: 99%